American Caesar, Douglas MacArthur, 1880-1964 - Manchester, William, 1922-2004 (Little, Brown and Company, 2008)
MacArthur, the public figure, the private man, the soldier-hero whose mystery and appeal created a uniquely American legend, portrayed in a brilliant biography that will challenge the cherished myths of admirers and critics alike.